2023
DOI: 10.3389/fpsyt.2023.1190084
|View full text |Cite
|
Sign up to set email alerts
|

Waiting for a digital therapist: three challenges on the path to psychotherapy delivered by artificial intelligence

Abstract: Growing demand for broadly accessible mental health care, together with the rapid development of new technologies, trigger discussions about the feasibility of psychotherapeutic interventions based on interactions with Conversational Artificial Intelligence (CAI). Many authors argue that while currently available CAI can be a useful supplement for human-delivered psychotherapy, it is not yet capable of delivering fully fledged psychotherapy on its own. The goal of this paper is to investigate what are the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 117 publications
0
10
0
Order By: Relevance
“…Even in remote online therapy, which was frequently practiced during the Covid pandemic, users with secure attachment showed online a better therapeutic alliance than those with insecure attachment ( Mercadal Rotger and Cabré, 2022 ). Whether avatars equipped with artificial intelligence are able to achieve this is questionable ( Grodniewicz and Hohol, 2023 ), as is whether these avatars can adapt to the respective hypnotizability of their patients. It can be assumed that there will continue to be a certain number of people who are highly hypnotizable and whose neurophysiological make-up goes beyond the effects of expectation and imagination.…”
Section: Discussionmentioning
confidence: 99%
“…Even in remote online therapy, which was frequently practiced during the Covid pandemic, users with secure attachment showed online a better therapeutic alliance than those with insecure attachment ( Mercadal Rotger and Cabré, 2022 ). Whether avatars equipped with artificial intelligence are able to achieve this is questionable ( Grodniewicz and Hohol, 2023 ), as is whether these avatars can adapt to the respective hypnotizability of their patients. It can be assumed that there will continue to be a certain number of people who are highly hypnotizable and whose neurophysiological make-up goes beyond the effects of expectation and imagination.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial intelligence (AI) has begun to be applied in multiple domains of mental health care in recent years, and many scholars wonder whether psychological interventions could be delivered someday by mental health chatbots in the ChatGPT era. However, there are still some challenges on the path to psychotherapy delivered by AI consisting of limited knowledge of the active ingredients of psychotherapy, therapeutic relationships delivered by non-human agents, and human-like AI being capable of delivering fully-fledged psychotherapy is undeveloped[ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Users may become overly reliant on chatbots, as they can access them 24/7 with just a click, potentially exacerbating addictive behavior[ 48 ]. Research has shown that autonomy is directly correlated with positive treatment outcomes and is common in effective treatment interventions[ 53 , 54 ] and that enhancing autonomy is important for reducing problematic social media use. Overcommunication with ChatGPT may lead individuals to reduce their communication and interaction with peers.…”
Section: Potential Riskmentioning
confidence: 99%